Balance and Physical Functioning in Patients After Head and Neck Cancer Post?Neck Dissection Surgery: A Case Series. - Broderick, Julie (My University, 2020)
Background and Purpose: Rehabilitation research in people with head and neck cancer, undergoing neck dissection (ND) surgery, has been largely confined to evaluation of shoulder dysfunction. Balance and broader physical functioning variables were evaluated in this patient group. Case Description: This case series presents four patients scheduled for ND surgery, who completed a comprehensive battery of balance and physical functioning assessments pre-operatively and six weeks post-operatively. Outcomes: Post-ND surgery, the majority (n=3) of patients reported increased upper quadrant pain, with proprioception and neck range of motion measurements showing a decreasing trend. One patient had no neck pain or changes in proprioception. The changes for standing balance and endurance varied across the patients, with no observable trend. Discussion: Quality of life, physical activity and a number of physical functioning measures, including proprioception and physical activity, were lower after ND surgery. This case series identifies the adverse effects of ND surgery performed prior to the start of adjuvant therapy, with many deficits noted potentially amenable to therapeutic intervention. The clinical implication of this study is that Physical Therapists should assess physical functioning variables after ND surgery and intervene early if deficits are noted.
PUBLISHED
Keywords: Head and neck cancer; Neck dissection; Neck proprioception; Standing balance; Physical Activity; Case series; Cancer; Chronic Health Condition; Physical disability